2018
DOI: 10.1177/2168479017745025
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reporting of Adverse Drug Reactions (ADRs): Survey of Public Awareness and Predictors of Confidence to Report

Abstract: Lack of awareness of the ADR monitoring system is still prevalent among Malaysian patients. The ease of completing the ADR form and education level are predictive of patient confidence to report ADRs. These factors should be considered in designing public promotional activities to encourage patient contributions to pharmacovigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
4
11
1
Order By: Relevance
“…The causes of acute drug poisoning in adults are complex, which are often related to the lack of awareness of personal medication safety and the toxic effects of the drug itself [ 1 ]. It refers to a drug poisoning event in which toxic drugs enter the human body through the respiratory tract, skin, mucous membrane, or digestive tract in a short time, causing damage to the patient's body and occurrence of multiple organ dysfunction, which has the characteristics of rapid onset, severe illness, and high mortality [ 2 , 3 ]. In recent years, its incidence in China has increased, accounting for about 6% to 8% of the total number of patients in the emergency department, which puts pressure on the diagnosis and treatment of the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of acute drug poisoning in adults are complex, which are often related to the lack of awareness of personal medication safety and the toxic effects of the drug itself [ 1 ]. It refers to a drug poisoning event in which toxic drugs enter the human body through the respiratory tract, skin, mucous membrane, or digestive tract in a short time, causing damage to the patient's body and occurrence of multiple organ dysfunction, which has the characteristics of rapid onset, severe illness, and high mortality [ 2 , 3 ]. In recent years, its incidence in China has increased, accounting for about 6% to 8% of the total number of patients in the emergency department, which puts pressure on the diagnosis and treatment of the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…We used the significant level at p < 0.1 to select variables for the univariate logistic regression analysis because, at a level of p < 0.05, variables known to be important would have been excluded [ 33 ]. Several other studies [ 34 – 36 ] also used the same level ( p < 0.01). Non-ordered categorical data with more than two levels (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Through the questionnaire survey, it can be said respondents' knowledge of ADR and its monitoring and reporting was incomplete. Other studies have shown similar results [29,35]. Studies [9,[39][40][41] show that the public (patients) and HCPs often ignore the criteria of reporting an ADR immediately upon suspecting an ADR, many individuals think that only serious ADRs that affect daily life or require hospitalization are worth reporting, or they only selectively report new ADRs, which will lead to underreporting.…”
Section: Discussionmentioning
confidence: 81%
“…ADRs reported by the public can complement those reported by HCPs, to add value to the pharmacovigilance system and generate new safety signals [6,18,19]. Globally, more than 40 countries have incorporated patient or consumer ADR reporting into their pharmacovigilance schemes [29,30]. In some countries like the United States, Canada, and New Zealand, consumers have been allowed to directly report ADRs since implementation of the pharmacovigilance plan [14,31].…”
Section: Introductionmentioning
confidence: 99%